Brain potentials indicate the effect of other observers' emotions on perceptions of facial attractiveness. (23rd March 2016) - Huang, Yujing; Pan, Xuwei; Mo, Yan; Ma, Qingguo
Highlights: Others' emotions would bias perceptions of facial attractiveness. Late positive potential was modulated by others' emotions. Social influence of others' emotions may be based on observational learning. Abstract: Perceptions of facial attractiveness are sensitive to emotional expression of the perceived face. However, little is known about whether the emotional expression on the face of another observer of the perceived face may have an effect on perceptions of facial attractiveness. The present study used event-related potential technique to examine social influence of the emotional expression on the face of another observer of the perceived face on perceptions of facial attractiveness. The experiment consisted of two phases. In the first phase, a neutral target face was paired with two images of individuals gazing at the target face with smiling, fearful or neutral expressions. In the second phase, participants were asked to judge the attractiveness of the target face. We found that a target face was more attractive when other observers positively gazing at the target face in contrast to the condition when other observers were negative. Additionally, the results of brain potentials showed that the visual positive component P3 with peak latency from 270 to 330 ms was larger after participants observed the target face paired with smiling individuals than the target face paired with neutral individuals. These findings suggested that facial attractiveness of an individual may be influenced by the emotional expression on the face of another observer of the perceived face.